Protection and parameter optimization of one-way surge tower for water conveyance pipelines under complex terrain conditions - Xiaoying Zhang; Chao Wang; Lin Li; Shaokang Bian (Scientific Reports)
Abstract The water hammer protection mechanisms for long-distance gravity-fed water transmission systems under complex terrain conditions remain inadequate. Current engineering practices commonly face issues such as insufficient negative pressure protection efficiency in multiple undulating pipe sections and a lack of theoretical basis for parameter matching of protective facilities, which seriously jeopardize the operational safety of water transmission pipelines. This paper focuses on gravity flow water pipelines with significant terrain undulation. Employing the characteristic line method, a hydraulic transition process calculation model is established to examine protection by combining air valves with one-way surge towers. Besides, the quantity of one-way surge towers is determined based on negative pressure improvement. The study subsequently optimizes parameters including the tower diameter, outlet diameter, and effective depth of the one-way surge towers. The results demonstrate that the negative pressure of the pipeline is not substantially enhanced by adding distinct numbers of one-way surge towers. Provide the ranking of factors affecting the suppression of water hammer negative pressure in a one-way surge tower. An optimal parameter scheme for one-way surge towers exists, under which the peak of the pipeline’s lowest negative pressure is substantially reduced while optimizing the overall negative pressure distribution of the pipeline. The practical engineering protection schemes and the derived configuration guidelines for protective facilities in this study provide both theoretical foundations and practical engineering guidance for the water hammer protection design in water transmission projects under complex terrain conditions.